Investment in schooling and the marriage market - Pierre-André Chiappori; Murat Iyigun; Yoram Weiss (Institute for the Study of Labor (IZA), 2006)
We present a model with pre-marital schooling investment, endogenous marital matching and spousal specialization in homework and market production. Investment in schooling raises ages and generates two kinds of returns in our framework: a labor-market return and a marriage-market return because education can affect the intra-marital share of the surplus one can extract from marriage. When the returns to education and household roles are gender neutral, men and women educate in equal proportions and there is pure positive assortative matching in the marriage market. But if men and women have different market returns or household roles, then there may be mixing in equilibrium where some educated individuals marry uneducated spouses and those who educate less extract a relatively larger share of the marital surplus. The existence of large and frictionless marriage markets creates competition among potential spouses, precludes bargaining and generates premarital investments that are efficient. Given that the gender wage gap narrows with the level of education, women's labor-market return from schooling is higher than that of men. Moreover, women's household time obligations have declined over time, raising their marriage-market return from schooling. Combining these two effects, we explain why women now attain higher schooling levels than men.
urn:nbn:de:101:1-20080702262
Keywords: 330; Schulfinanzierung; Bildungsertrag; Frauen; Männer; Bildungsniveau; Geschlecht; Familienökonomik